Faktor Penyebab Kejadian Pasien Pulang Atas Permintaan Sendiri di Ruang Rawat Inap - Nursyarifa; Samsualam; Fatma Jama; Andi Mappanganro (Window of Nursing Journal, 2025)
Patients who are forced to return home often occur in hospitals, which of course will have an impact on patients and the quality of hospital services. The aim of this research is to determine the factors that influence the incidence of patients returning home at their own request. This research is a quantitative research using a correlational study design with a sampling technique using Purposive Sampling, the sample size is 66 respondents and the research instrument uses the Chi-Square test. The results of the study showed that patients had treatment days >1 week (57.6%), 66 respondents had family support (100%), patients had less loyalty (53.0%), patients were forced to go home (42.4%). The test results show that there is an influence on the length of treatment on patients returning home at their own request, family support, and patient loyalty with each p value = 0.0001. Based on the research results, it can be concluded that length of treatment, family support and patient loyalty influence patients going home at their own request.